2004
DOI: 10.1002/jsfa.1871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cationization on DSC thermal profiles, pasting and emulsifying properties of sago starch

Abstract: Cationic sago starches were prepared using an aqueous alkaline process with different levels of cationic reagent 3-chloro-2-hydroxypropyltrimethylammonium chloride (0.01-0.10 M), sodium hydroxide (0.03-0.86 M) and reaction temperature (30-62 • C). The degree of substitution (DS), reaction efficiency, thermal and pasting properties of cationic sago starches were analysed. Emulsifying and fat binding properties of native sago starch, cationized sago starch and commercial chitosan were compared at two different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…This explains the higher clarity of HPSS at increasing degrees of substitution 28. Other substituted starches, such as cationic starch 29 and acetylated starch 23, also form clear pastes or gels.…”
Section: Resultsmentioning
confidence: 95%
“…This explains the higher clarity of HPSS at increasing degrees of substitution 28. Other substituted starches, such as cationic starch 29 and acetylated starch 23, also form clear pastes or gels.…”
Section: Resultsmentioning
confidence: 95%
“…Intrinsic viscosity decreased with increasing temperature, but the critical concentration remained fairly constant over the range of temperatures (Nurul et al 2001). Siau et al (2004) attempted to make cationic sago starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride (0.01-0.10 mol L −1 ) and sodium hydroxide (0.03-0.86 mol L −1 ) and found that the gelatinization enthalpy of cationic sago starch was lower, compared with native sago starch. The enthalpy of a transition is explained as corresponding to the amount of crystal order (or double helical structure) in the starch suspension (Mohamed et al 2008).…”
Section: Gelatinization Characteristics Of Sago Starchmentioning
confidence: 99%
“…The potential of using sago starch as a biomass source has been explored by Wang and others (1996). To further enhance the utilization of sago starch, modifications such as cross‐linking and hydroxypropylation (Wattanachant and others 2003), phosphorylation (Muhammad and others 2000), succinoylation (Sun and Sun 2002), carboxymethylation (Noor Fadzlina and others 2005), cationization (Siau and others 2004), and enzyme modifications (Wong and others 2007) have been carried out on sago starch. These processes can alter the properties of sago starch such that it might find further applications in the food industries as thickener, stabilizer, and texturizer (Bujang and Ahmad 2000).…”
Section: Utilization Of Sago Starchmentioning
confidence: 99%